2018
DOI: 10.1016/j.jaci.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial origin of eosinophilic esophagitis

Abstract: Eosinophilic esophagitis (EoE) is a chronic, allergen-driven inflammatory disease of the esophagus characterized predominantly by eosinophilic inflammation, leading to esophageal dysfunction. Converging data have placed the esophageal epithelium at the center of disease pathogenesis. In particular, the main EoE disease susceptibility loci at 2p23 and 5p22 encode for gene products that are produced by the esophageal epithelium: the intracellular protease calpain 14 and thymic stromal lymphopoietin, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(100 citation statements)
references
References 153 publications
(251 reference statements)
5
85
0
1
Order By: Relevance
“…Eosinophilic esophagitis (EoE) is considered a type 2 immune disease and often coexists with AD, asthma, and FA (13). The mucosa of the human esophagus is lined by the multilayer squamous nonkeratinized epithelium, which provides a protective barrier against environmental insults.…”
Section: Epithelial Barrier Dysfunction In Other Allergic Diseasesmentioning
confidence: 99%
See 2 more Smart Citations
“…Eosinophilic esophagitis (EoE) is considered a type 2 immune disease and often coexists with AD, asthma, and FA (13). The mucosa of the human esophagus is lined by the multilayer squamous nonkeratinized epithelium, which provides a protective barrier against environmental insults.…”
Section: Epithelial Barrier Dysfunction In Other Allergic Diseasesmentioning
confidence: 99%
“…These diseases have in common a dysfunctional epithelial barrier, resulting in the penetration of allergens and microbes, accompanied by the release of epithelial-derived cytokines (e.g., thymic stromal lymphopoietin [TSLP], IL-25, IL-33), which drive type 2 immune responses. Although other immune pathways can modify the course of illness, cytokines including IL-4, IL-13, IL-31, TSLP, and IL-33 play a key role in allergic diseases (4-8), eliciting local tissue injury and repair (5,(9)(10)(11)(12)(13)(14).AD is the most prevalent chronic inflammatory skin disease (3,(15)(16)(17)(18)(19). In a subset of allergic patients, it is thought that ADrelated skin epithelial dysfunction contributes to the atopic march, which starts with AD and often leads directly to FA (20-23).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The pathophysiology of EoE is thought to arise from the presence of food allergens in contact with the esophageal mucosa, which causes a T-helper type 2 (Th2) immune response leading to mucosal inflammation and eosinophilia, epithelial dysfunction, and long-term fibrosis. 1 Epithelial barrier dysfunction plays a critical role in this process because it promotes continued exposure to allergens and microbiota in the esophageal lumen, which stimulates epithelial cells and leukocytes to release chemokines and cytokines. 2,3 Decreased barrier integrity in EoE has been measured by loss of mucosal impedance in vivo and transepithelial electrical resistance in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its association with Castleman disease, eosinophilic granulomatosis with polyangiitis, and sarcoidosis, elevated IgG4 is thought to represent a marker of mucosal barrier breakdown, rather than a direct trigger. Genomewide association studies have identified several genes associated with epithelial barrier abnormalities through genetic and epigenetic mechanisms . Tissue eosinophilia has also been reported in other diseases, such as chronic rhinosinusitis with nasal polyps and nonallergic rhinitis with eosinophilia syndrome, where nonspecific inflammation has been suggested to result from antigen exposure in the setting of a primary epithelial barrier abnormality …”
Section: Discussionmentioning
confidence: 99%